Crises and the resilience of the aviation industry: a literature review of crises and airline responses - Cook, Daniel; Mayer, Robert; Doy, Gary (Elsevier, 2023)
This paper aims to identify major crises that airlines have faced across multiple regions of the world simultaneously, and the responses to them. To comprehend the present status of the literature on this topic, relevant publications are reviewed. Following the COVID-19 pandemic, the coverage of literature analysing airline responses to crises in academia has increased, with new literature emerging at a fast pace. To date, most of the literature that encompasses aviation has formed part of a wider study, usually on tourism, transportation, or hospitality. It normally analyses these fundamental issues generically from the perspectives of many organisations within these vast sectors, with little emphasis on airlines. However, there are only a few exceptions producing academic publications with airline crisis responses and resilience as their focus. This paper breaks down literature into different categories to appraise various types of crises, sourcing literature with a wide variety of methods, geographies, purposes and results. It finds little agreement in academia regarding the best way for an airline to respond to a crisis in a resilient manner. Nonetheless, the study finds that crises events act as a springboard for research into crisis response within the industry.
12th International Conference on Air Transport – INAIR 2023, The Future of Aviation – is the Sky the Limit? 15-17 November 2023, Tartu, Estonia
Keywords: Airlines; Crises responses